2017
DOI: 10.1021/acs.energyfuels.7b01007
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Analysis of Pore Network in Tight Gas Sandstones Using NMR Method: A Case Study from the Ordos Basin, China

Abstract: To characterize the pore structure and quantify fractal dimensions of tight gas sandstones, a case study is performed on the Lower-Middle Permian tight sandstones in the Ordos Basin in China by conducting a series of experiments including X-ray diffraction (XRD) analysis, routine petrophysical measurements, thin section and scanning electronic microscope (SEM) observations, and nuclear magnetic resonance (NMR) experiment. The studied tight sandstones mainly consist of quartz and clay minerals, and pore types i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 57 publications
3
68
0
Order By: Relevance
“…17 With the development of unconventional oil and gas, NMR is gradually applied to the study of the pore characteristics of unconventional reservoirs. [18][19][20] Yao et al applied the NMR to study the pore characteristics of coals and the strong correlation between transverse relaxation time T 2 and pore structures of coals were found; they used the T 2cutoff point to divide NMR T 2 spectrum and pore distribution models were established combining with MIP. 21 They also compared MIP, constant-rate-controlled mercury porosimetry, micro-CT and NMR for analyzing pore size distribution and found that NMR can better evaluate pore size distribution of coal under nondestructive conditions.…”
Section: Introductionmentioning
confidence: 99%
“…17 With the development of unconventional oil and gas, NMR is gradually applied to the study of the pore characteristics of unconventional reservoirs. [18][19][20] Yao et al applied the NMR to study the pore characteristics of coals and the strong correlation between transverse relaxation time T 2 and pore structures of coals were found; they used the T 2cutoff point to divide NMR T 2 spectrum and pore distribution models were established combining with MIP. 21 They also compared MIP, constant-rate-controlled mercury porosimetry, micro-CT and NMR for analyzing pore size distribution and found that NMR can better evaluate pore size distribution of coal under nondestructive conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The fractal dimensions have been widely employed to quantitatively characterize the complexity and heterogeneity of tight sandstone reservoirs [50]. Based on recent studies [27,44,51], the number of pores with sizes greater than r o (N r ) can be obtained as: where r is the pore radius (µm); r max is the maximum pore radius (µm); B is the fractal factor; f(r) is the density function of the pore radii and D is the fractal dimension of the pore space.…”
Section: Fractal Analysis Based On the Hpmi-nmr Integrationmentioning
confidence: 99%
“…Tight gas reservoirs are widely present in China; there are more than ten basins including Ordos, Sichuan, Shanxi, Songliao, and Tarim with extremely rich resource potential (Wu et al 2017a, b). However, it is also accompanied by the complex geological conditions, poor reservoir physical properties and strong reservoir heterogeneity (Shao et al 2017). Hydraulic fracturing must be implemented to obtain commercial gas production.…”
Section: Introductionmentioning
confidence: 99%